(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
Despite the growing use of digital applications in cultural heritage preservation, limited research exists on the comparative effectiveness of digital versus traditional display methods for preserving ethnic costume heritage. This study investigates how digital technologies influence the perception of Korean traditional costumes among China’s Korean ethnic minority (Chaoxianzu). Using CLO3D digital modelling and questionnaire surveys (n = 107), we found that digital display methods excel in communicating costume characteristics through three-dimensional visualisation and multi-angle presentation, with particularly strong evaluations for intuitiveness (81.31%) and colour representation (76.64%). Digital methods significantly enhance cultural understanding (75.70%) and stimulate innovative applications (70.09%), especially among younger audiences (85% positive response rate). Our findings reveal that digital and physical display methods serve complementary rather than competing roles—digital methods excel in accessibility and spatial representation (87.85% preferred for multi-angle observation). In comparison, traditional approaches provide essential tactile experiences, which are valued for their material experience (89.72%). Statistical analysis identifies 360^◦ multi-angle observation (β = 0.41) and magnified detail observation (β = 0.35) as the most critical technical factors affecting perception value. This research provides empirical evidence for developing integrated preservation strategies that combine digital technologies with traditional approaches to enhance the transmission and sustainable development of ethnic costume heritage.